Examining the Role of Fear of Missing Out in Shaping Online Impulsive Buying Behavior of Generation Z Students - Aulia Oktri Syafila; Desvi Yanti Mukhtar; Fasti Rola (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
This study examines the role of Fear of Missing Out in shaping online impulsive buying behavior among Generation Z students within digitally mediated consumption environments. Grounded in a qualitative conceptual approach, the research synthesizes findings from prior empirical studies, official reports, and theoretical literature to explore the psychological, social, and emotional mechanisms underlying impulsive purchasing behavior. The analysis reveals that Fear of Missing Out functions as a key psychological trigger that reduces self-control and heightens emotional urgency during online shopping. Social media dynamics, influencer presence, and algorithmic visibility further intensify this effect by normalizing rapid consumption and reinforcing social validation. Emotional regulation emerges as a critical factor, as impulsive buying frequently serves as a coping mechanism for social anxiety and perceived exclusion. Over time, these behaviors influence students’ financial patterns and increase vulnerability to compulsive consumption. The study contributes to a deeper understanding of Generation Z’s digital consumer behavior by highlighting how emotionally driven and socially reinforced processes shape impulsive buying decisions in contemporary online marketplaces..